Modulation of the maladaptive stress response to manage diseases of protein folding. - Daniela Martino Roth; Darren M Hutt; Jiansong Tong; Marion Bouchecareilh; Ning Wang; Theo Seeley; Johanna F Dekkers; Jeffrey M Beekman; Dan Garza; Lawrence Drew; Eliezer Masliah; Richard I Morimoto; et al. (PLoS Biology, 2014)
Diseases of protein folding arise because of the inability of an altered peptide sequence to properly engage protein homeostasis components that direct protein folding and function. To identify global principles of misfolding disease pathology we examined the impact of the local folding environment in alpha-1-antitrypsin deficiency (AATD), Niemann-Pick type C1 disease (NPC1), Alzheimer's disease (AD), and cystic fibrosis (CF). Using distinct models, including patient-derived cell lines and primary epithelium, mouse brain tissue, and Caenorhabditis elegans, we found that chronic expression of misfolded proteins not only triggers the sustained activation of the heat shock response (HSR) pathway, but that this sustained activation is maladaptive. In diseased cells, maladaptation alters protein structure-function relationships, impacts protein folding in the cytosol, and further exacerbates the disease state. We show that down-regulation of this maladaptive stress response (MSR), through silencing of HSF1, the master regulator of the HSR, restores cellular protein folding and improves the disease phenotype. We propose that restoration of a more physiological proteostatic environment will strongly impact the management and progression of loss-of-function and gain-of-toxic-function phenotypes common in human disease.